The aesthetics of structural patterns in the plastic products of the students of the Department of Art Education (Journal of the College of Basic Education, 2022)
The current research dealt with the study of the aesthetics of structural patterns in the plastic products of the student of the Department of Art Education through expressive and aesthetic artworks, as the structural patterns l are what we are looking for in the students’ drawings in an effort to clarify the structural patterns followed by them, and we can identify the aesthetics of structural patterns by linking beauty and art In philosophical thought to reach the structural patterns between concept and significance in plastic art through a good understanding of the express purpose of the artistic work, and thus the researcher adopted the descriptive research method, was adopted as it is the most appropriate method to achieve the goal of the research. The research includes a community of (40) technical products, a random sample of ( 4) technical products was selected, The research tool was designed based on the indicators of the theoretical framework and previous studies, and it included (6) main axes, and (15) sub axes. It is characterized by some reduction and simplification, thus forming a systemic formation based on technology.